2022
DOI: 10.3390/medicina58040502
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Cigarette Smoking and Influence of Associated Factors among Students of the University of Banja Luka: A Cross-Sectional Study

Abstract: Background and Objectives: Cigarette smoking among the youth population has increased significantly in developing countries, including Bosnia and Herzegovina. However, no extant literature assesses the prevalence of tobacco use, nor identifies factors associated with smoking. This study determined the prevalence of cigarette smoking among a specific cohort of students and assessed factors related to tobacco use in this population. Materials and Methods: This cross-sectional study included 1200 students at all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
1
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 31 publications
3
14
1
3
Order By: Relevance
“…Similar findings have been reported in a study conducted in Minia, Egypt, and a systematic review from Saudi Arabia 23 , 24 . Conversely, studies from Slovakia, Bosnia, and Portugal showed no significant association between sex and smoking 25 27 . The higher prevalence of smoking among male students in our study may be attributed to sociocultural and religious factors specific to Sudan.…”
Section: Discussionmentioning
confidence: 87%
“…Similar findings have been reported in a study conducted in Minia, Egypt, and a systematic review from Saudi Arabia 23 , 24 . Conversely, studies from Slovakia, Bosnia, and Portugal showed no significant association between sex and smoking 25 27 . The higher prevalence of smoking among male students in our study may be attributed to sociocultural and religious factors specific to Sudan.…”
Section: Discussionmentioning
confidence: 87%
“…Partial bans did not significantly impact the prevalence of smoking [ 49 ]. Worldwide, tobacco-use prevention measures remain focused mainly on adolescents and young people [ 50 ]. Targeted efforts among the socioeconomically disadvantaged groups are needed too [ 22 ].…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%
“…In addition, increased environmental exposure to tobacco or harmful alcohol use (i.e., socialization and social experiences in public spaces such as college campuses, workplaces, restaurants, bars, etc.) increases the risk of tobacco use and harmful alcohol consumption (Hennessy et al, 2019; Ibrahim et al, 2022; Stafylis et al, 2018; Todorović et al, 2022). Furthermore, the inability to effectively regulate oneself is also associated with harmful alcohol consumption and tobacco smoking (Robson et al, 2020).…”
Section: Introductionmentioning
confidence: 99%